1986
DOI: 10.1073/pnas.83.24.9759
|View full text |Cite
|
Sign up to set email alerts
|

Trans-activation of the human immunodeficiency virus long terminal repeat sequence by DNA viruses.

Abstract: To investigate whether DNA viruses can augment gene expression of the human immunodeficiency virus (HIV), cotransfection experiments were carried out in which a recombinant plasmid containing the HIV long terminal repeat (LTR) linked to the chloramphenicol acetyltransferase (CAT) gene was transfected into cultured cells along with plasmids containing DNA from various distinct classes of DNA viruses. Molecular clones containing JC virus, BK virus, lymphotropic papovavirus, bovine papilloma virus, type 1 herpes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
140
1
2

Year Published

1987
1987
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(146 citation statements)
references
References 33 publications
3
140
1
2
Order By: Relevance
“…Several other DNA viruses including herpes simplex virus 1 have also been shown to trans-activate the HIV promoter (16,17). As we observed with HCMV, the herpes simplex virus 1 IE region includes the trans-activating sequences.…”
Section: Discussionsupporting
confidence: 50%
“…Several other DNA viruses including herpes simplex virus 1 have also been shown to trans-activate the HIV promoter (16,17). As we observed with HCMV, the herpes simplex virus 1 IE region includes the trans-activating sequences.…”
Section: Discussionsupporting
confidence: 50%
“…SV40 multiplication in human tissue may be`helped' by complementing functions of other viral agents, such as JCV, BKV or HIV, or a combination of them, infecting the same hosts. It is worth noting that reciprocal transactivation occurs between HIV and JCV [43], SV40 and JCV [44] and other viral models [45].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is co-infection with other viruses, especially herpesviruses. Several studies have demonstrated the ability of secondary infectious agents to trigger HIV growth in vitro (Gendelman et al, 1986;Zagury et al, 1986;Mosca et al, 1987;Rando et al, 1987;Horvat et al, 1989). Clinical findings have served to focus attention on human cytomegalovirus (HCMV), an opportunistic pathogen that has been detected in a number of different immunodeficiency syndromes, including AIDS (Macher et al, 1983;Mintz et al, 1983) and HCMV viraemia parallels the progression of AIDS symptoms (Fiala et al, 1986).…”
Section: Introductionmentioning
confidence: 99%